An economic analysis of solar hybrid steam injected gas turbine (STIG) plant for Indian conditions. (22nd January 2015) - Immanuel Selwynraj, A.; Iniyan, S.; Polonsky, Guy; Suganthi, L.; Kribus, Abraham
Abstract: Steam injection for power augmentation is one of the significant modifications of gas turbines that has been commercialized for natural gas-fired applications. The primary objective of this work is to demonstrate that the installation of a solar hybrid steam injected gas turbine plant (STIG) for power generation could have a lower installed cost and lower solar levelized tariff compared to the solar-only thermal power plant while producing a comparable energy output. An economic evaluation is presented for the locations Indore and Jaipur in India under constant, variable power and mixed power scenarios. The levelized tariff (LT) of solar hybrid STIG plant ranges 0.24–0.26 /kWh, and the levelized tariff (solar only) or solar levelized tariff (SLT) of solar STIG plant ranges from 0.29 to 0.4 /kWh in constant power (CP) and variable power (VP) scenarios. In case of mixed power (MP) scenario, the range of LT varies from 0.16 to 0.21 /kWh for CP and VP modes basis. In this analysis, size of the solar STIG plant varies from 48 MW to 212 MW based on the steam to air ratio. The IRR and payback period varies between 12%–17% and 6.3–8 years for both CP and VP scenarios at Jaipur and Indore. Sensitivity analysis reports that the performance of the power plants depends, to a large degree, on boundary conditions such as fuel and equipment costs. Highlights: An economic evaluation of solar hybrid STIG plant for Indore and Jaipur is performed. The levelized tariff (LT) is calculated in constant, variable power and mixed power scenarios. Solar levelized tariff (SLT), IRR, payback period is assessed. Sensitivity analysis was conducted by varying the cost factors.